Assessment of risk factors in cardiac failure after myocardial infarction - Reddy, P. Vijaya Narasimha; Reddy, R. Jaya Prakash (International Journal of Research in Medical Sciences, 2018)
Background: Cardiac failure is a clinical syndrome that may result from any structural or functional cardiac disorders that impairs the pumping ability of the heart. Post infarction cardiac failure is one of the common complications of Acute Myocardial Infarction which is influenced by factors like extent of MI, Life style, associated co-morbid conditions. Methods: The present study comprises of 50 cardiac failure patients with history of MI in the past and who presented with myocardial infarction with cardiac failure were included in this study. This study was conducted at Rajivgandhi Institute of Medical Sciences, Kadapa, YSR District, Andhra Pradesh. The study was carried out for a period of 2 years. Informed consent was taken from each and every patient included in the study. Results: In our study 42 (84%) are males and 8 (16%) are females. Out of 50 patients 37 (74%) are smokers and 32 (64%) are alcoholics. In our study maximum number of patients i.e. 60% of the patients are sedentary in nature. Among 42 male patients 28 are having WHR >0.9 and 8 female patients WHR >0.8 is quite significant. Conclusions: Post MI cardiac failure is more common in males and sedentary lifestyles. Smoking, alcohol consumption and associated co morbid conditions have linear relationship with incidence of post infarction Cardiac failure. Abdominal obesity has positive effect on incidence of post MI cardiac failure.